PERBUATAN MELANGGAR HUKUM OLEH PEMERINTAH DALAM PERSPEKTIF HUKUM TATA NEGARA ISLAM - Jannah, Miftahul; Fatmawati, Fatmawati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
The concept of a walfare state has implications for the broader functions of the state. The expansion and application of government duties and functions sometimes causes harm to society, especially in the realm of public law. This study aims to understand the concept of unlawful acts by the government and the process of solving them with a normative legal approach and a syar’i approach. Unlawful acts by the ruler or government are government decisions or actions in the realm of public law that are contrary to laws and regulations and general principles of Good Governance that harm the community or civil legal entities, either in the form of exceeding authority, mixing up authority, and/or acting arbitrarily. The settlement of disputes over unlawful acts by the government is the authority of the General Court, which has then shifted to the competence of the State Administrative Court since the enactment of Supreme Court Regulation Number 2 of 2019. In Islamic law, there are several judicial institutions with different authorities, such as the tahkim institution, the al-hisbah institution, the madzalim institution, the qadha institution, and the qadhil qudha institution. However, specifically for the handling of disputes involving rulers with people, it became the authority of the madzalim institution.